(untitled) (Medical Forum Monthly, 2024)
Objective: Cone-beam computed tomography images were used in this investigation to locate the mandibular foramen based on the arch side. Study Design: This retrospective cross-sectional analysis examined hospital data. Place and Duration of Study: This study was conducted at the Khyber College of Dentistry's (KCD) Radiology Department, Peshawar, Pakistan. It was conducted from 4th November 2021 to 3rd May 2022. Methods: A radio-anatomical inquiry was conducted to assess 1000 CBCT photographs from patients who received evaluation during a two-year period. All statistical analyses of the data sets were conducted at a P≤0.05 level of significance. Results: Each CBCT scan included measurements of the mandibular foramens on both sides of the jaw, for 200 mandibular foramens in total (100 on the left and 100 on the right). With a range of 15 to 70 years, the mean age was 39.81±14.71 years. The experiment's findings demonstrated that the left or right side of the arch had no bearing on where the mandibular foramen was located. Conclusion: The investigation's findings demonstrated that the arch side had no bearing on where the mandibular foramen was located.